Pemberian Pupuk Kandang Ayam dan Pupuk Organik Cair Biotogrow untuk Meningkatkan Pertumbuhan dan Produksi Bawang Merah (Allium ascalonicum L.) - Marya Sukma Dewi; Ahmad Sofian; , Farida Hariani (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Al Azhar Medan, 2023)
The goal of this research was to find out how well chicken manure and biotogrow liquid organic fertilizer worked together to boost the development and yield of Shallots (Allium ascalonicum L.). The experimental design was a randomized factorial block with 2 variables and 3 replications, where the first component was the number of times chicken manure was applied (A), with 3 values (none, medium, and high). A0 = no treatment (control), A1 = 1.3 kg plot-1, and A2 = 2.6 kg/plot. The second factor was giving biotogrow (B), consisting of 4 levels, namely B0 = no treatment (control), B1 = 1.5 ml L-1 of water, B2 = 3 ml ml L-1 of water, and B3 = 4.5 ml L-1 of water. Observed variables included plant height (cm), the number of tillers per cluster (strands), and tuber weight per plot (g). The study revealed that the application of poultry manure had a significant effect on the parameter of tuber weight per plot, but not on the parameters of plant height or number of tillers per clump. The application of bio-grow had a significant impact on the parameter of tuber weight per plot, but not on the parameters of plant height or number of tillers per hill. The interaction between the two treatments had no significant effect on any of the measured parameters.